Learning Levels and Gaps in Pakistan - Das, Jishnu (World Bank, Washington, DC, 2012)
The authors report on a survey of primary public and private schools in rural Pakistan with a focus on student achievement as measured through test scores. Absolute learning is low compared with curricular standards and international norms. Tested at the end of the third grade, a bare majority had mastered the K-I mathematics curriculum and 31 percent could correctly form a sentence with the word "school" in the vernacular (Urdu). As in high-income countries, bivariate comparisons show that higher learning is associated with household wealth and parental literacy. In sharp contrast to high-income countries, these gaps decrease dramatically in a multivariate regression once differences between children in the same school are looked at. Consequently, the largest gaps are between schools. The gap in English test scores between government and private schools, for instance, is 12 times the gap between children from rich and poor families. To contextualize these results within a broader South Asian context, the authors use data from public schools in the state of Uttar Pradesh in India. Levels of learning and the structure of the educational gaps are similar in the two samples. As in Pakistan, absolute learning is low and the largest gaps are between schools: the gap between good and bad government schools, for instance, is 5 times the gap between children with literate and illiterate mothers.